2022
DOI: 10.1101/2022.03.30.486354
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of Replication-induced Chromosomal Copy Numbers in Spatio-temporal Gene Regulation and Evolutionary Chromosome Plasticity

Abstract: For a coherent response to environmental changes, bacterial evolution has formed a complex transcriptional regulatory system comprising classical DNA binding proteins sigma factors and modulation of DNA topology. In this study, we investigate replication-induced gene copy numbers - a regulatory concept that is unlike the others not based on modulation of promoter activity but replication dynamics. We show that a large fraction of genes are predominantly affected by transient copy numbers and identify cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(62 reference statements)
1
1
0
Order By: Relevance
“…This is in accordance with previous findings which show that bacterial cells are able to recall distinct global expression patterns based on their stage of growth by the spatio-temporal regulation of chromosomal macrodomains [32]. While replication induced transient changes in actual copy numbers are a factor directing genomic transcription biases along the oriC/ter axis [33], the regulation of macrodomains occurs for functionally similar genes through direct DNA topology and transcriptional control. While in trans expression systems are per definition not affected by positional effects of the promoter of interest (as they are taken out of their natural, genomic context), they are partially affected by DNA topology [34] (e.g.…”
Section: Novel Promoters For the Use In Curvibacter Show Distinct Tem...supporting
confidence: 93%
“…This is in accordance with previous findings which show that bacterial cells are able to recall distinct global expression patterns based on their stage of growth by the spatio-temporal regulation of chromosomal macrodomains [32]. While replication induced transient changes in actual copy numbers are a factor directing genomic transcription biases along the oriC/ter axis [33], the regulation of macrodomains occurs for functionally similar genes through direct DNA topology and transcriptional control. While in trans expression systems are per definition not affected by positional effects of the promoter of interest (as they are taken out of their natural, genomic context), they are partially affected by DNA topology [34] (e.g.…”
Section: Novel Promoters For the Use In Curvibacter Show Distinct Tem...supporting
confidence: 93%
“…It has been confirmed that the genes that are closer to the origin site ( ori proximal gene) are replicated first and are more highly expressed ( 26 , 27 ). In E. coli , higher expression of oriC-proximal genes has been discovered on the chromosome, which is caused by the replication-induced increase of copy numbers (up to eight copies) of the oriC proximal region ( 28 , 29 ). However, we did not find any evidence in previous studies about this phenomenon in the expression of genes in plasmids, which should be validated in the future.…”
Section: Discussionmentioning
confidence: 99%